Analysis of Cavitation-induced Vibration Characteristics of a Vortex Pump Based on Adaptive Optimal Kernel Time-frequency Representation - Y. Wang; P. Zhou; C. Zhou; W. Zhou; J. Li (Journal of Applied Fluid Mechanics, 2024)
Cavitation-induced vibration presents a significant challenge in vortex pumps, leading to potential damage to hydraulic components and adverse effects on pump performance. This study aims to investigate the long-term implications of such phenomena. To capture the vibration signals caused by cavitation, we utilized vibration acceleration sensors on the vortex pump and collected data at five predetermined measuring points under three different operating conditions. The analysis used two prominent techniques, fast Fourier transform (FFT) and adaptive optimal kernel time-frequency representation (AOK-TFR), to explore the frequency-domain and time-frequency characteristics of the vibration signals. The findings reveal a notable increase in frequency amplitude at each monitoring point as the flow rate rises. Under cavitation conditions, pronounced vibration characteristics are observed along the y-axis and z-axis of the volute, with maximum vibration intensities of 1.83 m/s² and 1.80 m/s², respectively. The frequency amplitude exhibits non-constant behavior in the time series. Moreover, variations in the time-frequency characteristics are identified with changing flow rates. A distinct signal with a frequency of 750 Hz manifests in the x-axis and y-axis of the volute when the head experiences a 3% reduction from the cavitation level.